2016
DOI: 10.1007/s00068-016-0656-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-concussive syndrome after mild head trauma: epidemiological features in Tunisia

Abstract: The two most important findings of this study were the huge proportion of patients having minor head injury and discharged from ED without any explanation of possible symptoms after head trauma and the unknown impacts on life activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Studies have suggested that somatic domain PCSs (eg, headache and dizziness) are most commonly reported during the acute phase (<1 week postinjury), whereas cognitive and affective domain PCSs are more common during the subacute and chronic postinjury phases for young adults following an mTBI. 23,24 Our findings suggest a similar phenomenon in the acute phase; however, cognitive symptoms (not affective ones) were dominant in the chronic phase among older adults with mTBIs. Copyright © 2021 Wolters Kluwer Health, Inc.…”
Section: Discussionsupporting
confidence: 55%
“…Studies have suggested that somatic domain PCSs (eg, headache and dizziness) are most commonly reported during the acute phase (<1 week postinjury), whereas cognitive and affective domain PCSs are more common during the subacute and chronic postinjury phases for young adults following an mTBI. 23,24 Our findings suggest a similar phenomenon in the acute phase; however, cognitive symptoms (not affective ones) were dominant in the chronic phase among older adults with mTBIs. Copyright © 2021 Wolters Kluwer Health, Inc.…”
Section: Discussionsupporting
confidence: 55%
“…The framework we have articulated is largely based on the empirically established premise that there is a stereotyped pattern of injury in mTBI 1315,21,24 . At the same time, there is a wide range of inter-individual variability across the acute, sub-acute, and chronic phases of post-concussive recovery in terms of the pattern of signs and symptoms 6669 . Our findings reinforce what is common across m/TBI 15,19,21 , in a way that is grounded in the biomechanics of shear wave propagation through tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Chakroun-Walha et al on "Post-concussive syndrome after mild head trauma-epidemiological features in Tunisia" demonstrates the ability but also the difficulties in the management of minor head injuries in situations with reduced resources [9].…”
mentioning
confidence: 99%